AN ANALYSIS OF STUDENTS GRAMMATICAL ERRORS IN TRANSFORMING AFFIRMATIVE TO NEGATIVE AND INTERROGATIVE SENTENCE OF SIMPLE PAST TENSE BY THE FIRST GRADE STUDENTS OF SMA NEGERI 1 SIPORA - Yashinta Martaria Br Silaban; Feby Meuthia Yusuf; Lailatul Husna (Ekasakti Educational Scientific Journal, 2024)
The purpose of this research was to find out grammatical errors transforming affirmative to negative and interrogative sentence of simple past tense made by the first grade students’ of SMAN 1 Sipora. In this research, the population was the first grade students of SMAN 1 Sipora, the number of the population members was 84 students. The sample of this research was class X MIPA 2, and the size of the sample was 30 students. The method used in this research was descriptive analysis method to describe students’ errors and analysis the data by using formula: method to describe students’ errors and analyze P = × 100 %. The data was taken from the test; it was grammar test. The test contains 25 questions, every question was devided by into 3 parts, negative sentences, yes/no questions, and WH questions. The result of analyzing data showed that there were grammatical errors made transforming affirmative to negative sentence of simple past tense made by the first grade students of SMAN 1 Sipora. The researcher devided grammatical errors into four types. They were 217 omission errors (30.7%), 269 addition errors (38.1%), 80 misformation (11.33%), and 140 misordering (19.83%)